A Study on Consumer Perception - A Case Study for Laptops - Ranjith, P. V.; Goyal, Ela (Indian Journal of Marketing, 2011)
Laptops come in all kinds of shapes and sizes, each with its own set of pros and cons. While the smallest laptops are the most portable, they also have smaller keyboards and displays, fewer features, and slower performance than their bulkier brethren. Conversely, more full-featured laptops are generally more difficult to carry and take up more space on your desk and in your bag. Until they make the perfect laptop, the consumer has to sacrifice something. So the consumer has to think about what's most important - computing power, a complete set of features, long battery life, good looks, brand, a small form factor, or a low price etc. This study is aimed at understanding the consumer perception as to what are they looking for when they buy a laptop. The study also tries to find out if there is any correlation between the consumer's lifestyle and his laptop preferences. The study would be useful for all the laptop manufacturing companies and laptop retailers.